Testing the endowment effect for default rules - Isabel Marcin; Andreas Nicklisch (Max Planck Institute for Research on Collective Goods, 2014)
This paper explores potential endowment effects of contractual default rules. For this purpose, we analyze the Hadley liability default clause in a model of bilateral bargaining of lotteries against safe options. The liability default clause determines the right for the safe payoff option. We test the model in series of laboratory experiments. The results reveal a substantial willingness-to-accept to willingness-to-pay gap for the right to change lotteries against safe options. Even if we apply the incentive compatible Becker-DeGroot-Marschak value elicitation mechanism, there is a significant gap indicating a robust endowment effect caused by default rules. Differences of expected values of the lotteries and the safe options consistently decrease the gaps. Implications for applications of default rules in the law are discussed.
Keywords: K00; C91; K12; 330; Default rules; Endowment effect; Lotteries